Temporary improvement of motor symptoms of a patient with Parkinson's disease after accidental electric shock - Case report - Antônio Marcos Da Silva Catharino; Kattiucy Gabrielle Da Silva Brito; Edarlan Barbosa Dos Santos; Gilberto Canedo Martins; Marco Antonio Orsini Neves (Global Journal of Rare Diseases - Peertechz Publications, 2020)
Despite parkinson's disease to be one of the most frequent movement disorders, with motor and non-motor symptoms and pharmacological and surgical treatments, we present a case of temporary improvement of motor symptoms after an accidental electric shock and we highlight the need for furthrer studies to discuss possible mechanisms involved in this case.